Anatomi dan Anomali Kepatuhan - Banua, Raudal Tanjung (MAARIF Institute, 2023)
In national and state life, we are under the auspices of a constitution which is supported by a mutual commitment and consensus to obey each other. Ironically, the state, in this case power, along with mainstream culture, tends to be hegemonic which makes the anatomy of societal obedience sometimes at the point of anomaly. The state, through the party in power, can subtly adapt the consensus, if necessary to circumvent the constitution, for the sake of the group’s interests. Meanwhile, mainstream culture creates mass tastes, capitalizing on values because there is large capital and access. Anticipating this, if in politics there is an opposition system that balances the policies of the party in power, then in culture (necessarily) there is a counter-culture. Fighting culture is an alternative way to get out of oppressive and dominant conditions. Including national political phenomena and cultural politics. The following article examines various forms of counterculture directed against hegemonic centers, such as in literature and culture. This is no exception to Buya Ahmad Syafii Maarif’s unique fighting culture: fighting while keeping the foundations of the nation upright.